ANALISIS KOMPARATIF PENDAPATAN PENGOLAHAN KOPRA ASAP DAN KOPRA PUTIH DI DESA LIWUMETINKI KECAMATAN PASIR PUTIH KABUPATEN MUNA : Kata kunci: Pendapatan; Jemur; Putih - azelia monica; Muhamad Noor Azizu (Innofarm:Jurnal Inovasi Pertanian, 2023)
Copra is one of the results of smallholder plantations which, if managed properly, will provide good income for farmers. This study aimed to determine the magnitude of the difference in income, cost, and feasibility in processing between copra as soon as possible and white copra in Liwumetinki Village, Pasir Putih District, Muna Regency. This research was conducted in August-October 2022 with 11 smoked copra processing farmers and ten white copra processing farmers as respondents. The data used in this research is primary data from interviews with copra farmers. The average total cost of production in processing smoked copra is Rp. 4,330,563 with an income of Rp. 1,201,437, while white copra is Rp. 3,992,685 with an income of Rp. 1,107,315. The R/C ratio value of the two copra products is 1.2, with a profit value of 0.2, indicating the development's feasibility. Meanwhile, based on the comparative value of t count (3.135) > t table (3.75) obtained shows that the income from copra processing is immediately higher than the income from white copra processing.